Health education of parents in the field of immunization - Salwa, Agata Anna (Journal of Education, Health and Sport, 2017)
Admission. Vaccination, as one of the top achievements in medicine, is an important part of health policy implementation at national and global level. Regular immunization of children and adults has improved quality and prolonged life expectancy. Aim of the job. The purpose of the work was to show the need for parental health education in the field of preventive vaccination. Brief description of knowledge. Health education and prevention of infectious diseases is an important priority among recommended preventive measures. One of the conditions for successful implementation of preventive vaccination is professional vaccination education. Summary. Education of parents in the field of immunization may be a desirable direction in the dissemination, development of active immunization.